(untitled) (Architecture Image Studies, 2025)
This research presents an analytical jurisprudential study of zakat on shares in-joint-stock companies. It explores key elements, including the nature of shares, their jurisprudential classification, and the impact of a shareholder’s intention on the zakat obligation for company shares. The study aims to achieve several objectives, primarily determining who is obligated to pay zakat on shares in companies and identifying the entity responsible for its payment. The findings highlight that zakat on shares is a legal necessity, ensuring the protection of the rights of the poor and safeguarding the integrity of zakat as a fundamental pillar of Islamic finance. Neglecting its proper implementation could lead to the misallocation or loss of zakat funds. Based on these findings, the study strongly recommends the activation and enforcement of zakat payment on shares in joint-stock companies to uphold its intended social and economic impact.